On Non-Comaximal Graphs of Ideals of Commutative Rings - Barman, Bikash; Rajkhowa, Kukil Kalpa (Armenian Journal of Mathematics, 2023)
In this paper, we relate some properties of non-comaximal graph of ideals of a commutative ring with identity with the properties of the ring.